Challenges and opportunities of clinical pharmacists during COVID-19: A review of the literature - Abrar K. Thabit, Jimmy Jose (Journal of Applied Pharmaceutical Science, 2022)
The success and sustainability of any profession can be evident during times of crises. Clinical pharmacists adapted and adopted multiple roles, which were an extension of their routine activities including a few new activities depending on the situation demands. Numerous studies in the literature discussed the various roles played and the activities offered by clinical pharmacists during the coronavirus disease of 2019 (COVID-19) pandemic. The challenges and opportunities faced by the clinical pharmacists during this time are worth contemplating. We aimed to summarize the challenges faced by clinical pharmacists during the pandemic and the opportunities that arose. Providing direct patient care, change in scheduling, and burnout were among the top challenges. Telehealth services and participation in guideline development and education were among the prominent opportunities. A discouraging finding was the lack of adequate recognition along with other front-line workers. The pandemic was a clear indicator of the significant role a clinical pharmacist plays in the healthcare team. Measures need to be taken by clinical pharmacists to ensure authorities are well-informed of their activities. It is also recommended to incorporate these experiences in pharmacy degree programs to ensure that pharmacists are better prepared for any future health or natural crises.
Keywords: Clinical pharmacy, clinical pharmacist, COVID-19, coronavirus disease, SARS-CoV2